Pengaruh Gas C02 dan Refrigeran Dalam Udara Terhadap Efisiensi PLTS (Pembangkit Listrik Tenaga Surya) - Muh. Yusuf Yunus; Laurasti Aswindah Sari (Politeknik Negeri Ujung Pandang, 2019)
Application of sunlight energy every time is increasing along with the knowledge that continues to develop over time. One of the sources of solar energy is the Solar Power Plant (PLTS) which uses solar energy for electrical energy. The purposes of this research are to study the effect of CO2 gas for increasing the energy of PLTS and to find the effect of refrigerant gas on the efficiency of PLTS. Data is collected in an integrated electrical laboratory, the data are the voltage, current and intensity of solar radiation. Then the input power, output power and efficiency are calculated. The results of this study are the effect of CO2 gas on the efficiency of PLTS was not affect the efficiency of PLTS, namely the light intensity of 100 W / m2 to 380 W / m2 with a gas contribution of 5% and 10%, can be seen that if output power increase, the efficiency of PLTS is also increase. When using CO2 gas, the efficiency of PLTS almost the same as normal conditions (without gas). The effect of the refrigerant gas mixture was not enfluence the efficiency of PLTS. When using refrigerant gas of 5% and 10% both R22 and R134 the efficiency of PLTS was the same with CO2 gas which its efficiency almost the same as normal conditions (without gas). Data with the intensity of solar radiation 100 W/m2 in normal conditions (without gas) the maximum efficiency that can be obtained is 9.085917% with an output power of 1.061917 watts, when R134 and R22 gas were added at PLTS, it was obtained maximum efficiency at R134 (13,624637% )